Symptoms of allergic rhinitis in children with adenotonsillar hypertrophy - Davari, Rahim; Pirzadeh, Akbar; Amani, Firouz; Masoumi-Aval, Sheida (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: A few studies have been performed on whether allergic rhinitis is a cause of adenotonsillar hypertrophy. The aim of this study was to determine the symptoms of allergic rhinitis in children with hypertrophy. Methods: This descriptive cross-sectional study has been conducted on 150 patients’ candidates for adenotonsillectomy. The necessary information was collected through checklists and patient records. Results: A total of 150 patients were included in the study. In terms of gender, the highest frequency was related to boys (66.7%). Most of patients lived in the Ardabil (66.7%). The mean age of the subjects was 7.55 years. The highest frequency was related to the history of recurrent middle ear infection in children with 73 cases (48.7%). The lowest frequency was jointly assigned to the history of taking anti-allergy drugs and the history of recurrent itching in the child each with 21 cases (14%). There was no significant relationship between any of the studied symptoms and age and gender of patients. Most of patients with 90.7% had allergic rhinitis symptoms. Conclusions: Results showed that frequency of symptoms of allergic rhinitis in patients with adenotonsillar hypertrophy was in moderate level and the rate of it in studied patients was similar to its rate among general population.